Waste glass as a partial replacement for fine aggregates in controlled low strength material (CLSM) applications - Sadural, Alaisa Joyce V.; Teng, Cheyenne V.
This research proposed an alternative to conserve construction materials (fine aggregates) while utilizing scrap materials (waste glass) in controlled low strength material (CLSM). It aimed to determine the physical characteristics of waste glass, investigate the effects of varying water-to-cement ratio (W/C) and varying % glass replacement on the compressive strength of concrete, and to assess applicability of the resulting concrete mixtures. Results showed that for 1.1, 1.3, and 1.5 W/C, the compressive strength increases until it yielded highest mean of 258.89 psi, 357.57 psi, and 433.96 psi respectively at 20% glass replacements. Then it decreases thereafter. With 95% confidence level using two factor ANOVA with replication showed that varying the % glass replacements (P-value of 0.0000026) and W/C (P-value of 0.0000203) have significant effect while the interaction of both factors (P-value of 0.78) have no significant effect on the compressive strengths of the samples. Also, the strength is indirectly proportional to W/C and directly proportional to age of curing. Flowability is directly proportional to % glass replacement and W/C. While unit weight should be indirectly proportional to % glass replacement, it is not evident in this study. CLSM can be applied in backfill, pipe bedding material, structural fill, and pavement bases. Further studies can explore analysis of varying W/C and % replacement, in-depth microstructure analysis to fully explain the mechanical behavior of the design samples, comparison of economic analysis between conventional mixture and mixture with waste glass replacement, % glass replacements with lightweight aggregates, and different types of waste glass.